La violación del derecho del derecho a la protección de datos de carácter personal y las garantías constitucionales. - Chicaiza Mullo, Paulina Esthefania (2022)
In this research work, a detailed analysis is carried out of the different scenarios of violation of constitutional rights in regard to the protection of personal data conceived under a jurisdictional guarantee in order to protect the personal information of citizens; the right to personal privacy and honor, demanding that all public and private institutions be able to provide people with the required information in a clear and precise manner as requested; Therefore, cases have been evidenced in which these rights are violated, being already common in society, so from the doctrinal and practical approach, verify if the sentences of the Constitutional Court are governed by the principles contained in the Constitution, Law of Jurisdictional Guarantees and Constitutional control and International Instruments and Treaties. In order to meet the objectives proposed in this research work, the basic concepts of the importance of jurisdictional guarantees have been compiled, since it was analyzed based on the constitutional precepts and the infra-constitutional norms of our legal system, in addition to the relevant application of constitutional jurisprudence as a primary source of law where judges cease to be mouthpieces of the law but, through their binding rulings, create law; reasons why, through investigation, it can be determined that Habeas Data as a jurisdictional guarantee is effective and immediate when there are abuses in the database of the personal information of all individuals.